Cross-Canada Survey of Resistance of 2747 Aerobic Blood Culture Isolates to Piperacillin/Tazobactam and Other Antibiotics - Kevin R Forward; Patricia A Franks; Donald E Low; Robert Rennie; Andrew E Simor; the Canadian Piperacillin/Tazobactam Study Group (Canadian Journal of Infectious Diseases)
OBJECTIVE: To compare the activity of piperacillin/tazobactam with that of other broad parenteral antibiotics against aerobic and facultative anaerobic blood culture isolates in a Canada-wide survey.